PENGOLAHAN LIMBAH CAIR TAHU MENGGUNAKAN BIOREAKTOR ANAEROB SATU TAHAP DAN DUA TAHAP SECARA BATCH - Florence T.N. Silalahi, Halimatuddahliana, Amir Husin (Jurnal Teknik Kimia USU, 2018)
This research aimed to study the effect of one stage and two stage anaerobic fermentation on the performance of bioreactors in tofu liquid waste treatment. This research started with acclimatization that is adaptation process of microorganism derived from cow dung with tofu liquid waste. Acclimatization is carried out in acid condition (pH 5.5) and in neutral condition (pH 7). This is followed by a batch bioreactor operation for 40 days for one stage anaerobic fermentation (pH 7), while for the first stage of the two stage anaerobic fermentation (pH 5.5) lasted two days and proceeds with the second stage of the two stage anaerobic fermentation (pH 7) lasts 38 days The results obtained were COD removal efficiency of 76.6% for one stage anaerobic and 83.05% for two stage anaerobic. While the VFA concentration in the first stage of the two stage anaerobic increased by 33% of the one-stage anaerobic VFA concentration. One-stage anaerobic biogas yield of 0.24 L/g CODconverted and 0.27 L/g CODconverted for to two stage anaerobic.